Pelacakan Gen Aerolysin dari Aeromonas hydrophila pada Ikan Mas yang Diberi Pakan Ekstrak Bawang Putih (DETECTION OF AEROLYSIN GEN FROM AEROMONAS HYDROPHILA IN COMMON CARP FED WITH GARLIC EXTRACT) - Lukistyowati, Iesje; ., Kurniasih (Jurnal Veteriner, 2012)
Aeromonas hydrophila is a gram negative and opportunistic bacteria, which could cause fish mortalityin a short time from 80%-100%. One virulent factor of A. hydrophila on common carp (Cyprinus carpio L)that could cause fish mortality is aerolysin. This research used a synthetic primers of oligonukleotide todetect aerolysin, a specific genomes of A. hydrophila on common carp (Cyprinus carpio L). The commoncarps have been feed a woof that contain garlic extract during 30 days before they challenged with A.hydrophila. Polymerase Chain Reaction (PCR) was used to detect an aerolysin gen from A. hydrophila. Theelectrophoresis result showed aerolysin gene of Aeromonas hydrophila from Veterinary Faculty of GadjahMada University (FKH-UGM) isolate was amplified with 462 bp of molecule weight. While the aerolysingen was detected in the fish kidney with 900 bp of molecule weight. Further, DNA sequence analysis of thePCR product of A. hydrophila from FKH – UGM isolate showed homolog with isolate A. hydrophila subsphydrophila ATCC 7966 complete genome with score 55.4 (71%).
Keywords: Aeromonas hydrophila, Cyprinus carpio L, Garlic extract, PCR, DNA Sequencing